TINJAUAN HUKUM ISLAM TERHADAP PERAN ISTRI YANG BEKERJA PADA MALAM HARI DALAM MEWUJUDKAN KEHARMONISAN KELUARGA (Studi Kasus Perawat yang Sudah Berkeluarga di Rumah Sakit Islam Sunan Kudus Kabupaten Kudus) - Radhita Armand; Muhammad Muhammad (JOURNAL SAINS STUDENT RESEARCH, 2025)
This thesis aims to answer the problem of how the role of wives who work at night as nurses at the Sunan Kudus Islamic Hospital, Kudus Regency. This thesis uses a type of empirical legal research which is a legal research method by examining the applicable legal provisions in the form of Islamic law and what happens in reality in society or research conducted on the actual conditions that occur in society, with the intention of finding facts that are used as research data in the form of interviews. The results of this study concluded that: first, wives who work as nurses have a role as wives and also mothers, they must be able to divide their time between work and household affairs. Second, a wife who works at night is allowed because Islam does not prohibit it as long as she gets the approval of her husband and on the condition that a wife must not violate Islamic law and not neglect her household obligations